Malaysia Stock Market Integration: The Effect of Leader and Emerging Market - Ramdhan, N.; Mohamed Yousop, N. L.; Ahmad, Z.; Abdullah, N. M. H. (Journal of Advanced Research in Business and Management Studies, 2020)
A significant change in Gross Domestic Product (GDP) usually has a significant effect on the stock market. Recently, China, South Korea and Malaysia are listed as the best of emerging markets countries with the average growth of GDP’s of 5% and above (Bloomberg, 2014). For the year 2015 and 2016, India’s GDP is expected to grow roughly 8% to 9%, which is one of the highest growth rates worldwide (Goldman Sachs, 2015). Despite the increasing growth in the emerging countries, however, for the past few years, United States (U.S), Europe and Japan had indeed been recognized as a leader in the global stock market. With the existence of these leaders, it is in fact indirectly gives the idea that the world's stock markets to some extent are influenced by them. Thus, due to this scenario, this paper aims to shed lights on the real integration and relationship between market leaders with Malaysian stock market. Based on the empirical analysis from 1994 to 2014, results shows that the US stock market (DJIA) and the Indian stock market (BSE) are financially integrated with Malaysian stock market. However, Japan stock market (NIK) and China stock market (SHCI) are not financially integrated with Malaysian stock market (KLCI).